Biomonitoring of Water Quality by the Use of Aquatic Macroinvertebrates of the Mahan River in Singrauli, Madhya Pradesh, India - Pachu, Anish V.; Kumar, Sudhir; Mohan, V.; Jeeva, V. (Indian Forester, 2021)
Aquatic macroinvertebrates in the perennial/seasonal streams of the River Mahan in the Mahan Reserved forest in Singrauli district, Madhya Pradesh were sampled semi-quantitatively with a view to ascertain biological water quality by employing the Macroinvertebrate Water Quality Index (MWQI). The study identified 747 individuals of macroinvertebrates comprising of 32 taxa belonging to 10 orders and 28 families with Ephemeroptera (57%) and Odonata (54%) as the dominant taxa respectively during monsoon and summer. Abundance and richness of macroinvertebrates were relatively high during summer than during the monsoons. Among the Biotic Indices of macroinvertebrates used for bio-monitoring, the Taxa Tolerance Score (TTS) indicated 'good' with 'clean, but slightly impacted' water quality, that of the Average Score Per Taxon (ASPT) was 'moderate' and the Macroinvertebrate Water Quality Index (MWQI) indicated 'fair' water quality with 'significant pollution' respectively during both the sampling seasons. This study has improved the authors' knowledge about aquatic biodiversity of the water course and to improve the evaluation of water quality by employing biotic indices based on macroinvertebrates.